Saúde e saneamento : uma avaliação da abordagem da promoção de saúde em planos municipais de saneamento básico - Amanda Cristina Nunes Pacifico (2020)
Throughout history or in sanitation, we have taken on several approaches and ways of relating to health, in Brazil, it is remarkable as the first two decades of the 20th century, a period known in the Sanitation Era, as well as its institutionalization in the 1960s and 1970 as a precise urban structure for the structuring of cities. However, the sanitation legislative framework (Law nº 11.445 / 2007) determines that there is an articulation between sanitation policies and actions with urban and regional development of social interest, such as health promotion policies. In this sense, this study had the general objective of analyzing how the planning process in basic sanitation in small municipalities addresses a relationship of health and sanitation. A quantitative and qualitative research was carried out, through the analysis of Municipal Basic Sanitation Plans (PMSB) existing in Minas Gerais; terms of reference used in the construction of these plans and in Law No. 11,445 / 2007 with a focus on health approaches. Initially, small municipalities with PMSB (total of 286) were selected; later, an active search for PMSB was carried out, including 197. Through the sample calculation 74 PMSB were analyzed. From this sample, four terms of reference used in the construction of plans were used. After this stage, a floating reading of the documents was carried out and four PMSBs were selected. The documents were submitted to content analysis in order to identify the possible approaches presented through categories of analysis: (i) Concept of health; (ii) Objectives of the sanitation projects; (iii) Sustainability of actions and benefits; (iv) Articulation between policies, institutions and actions; (v) Technical and non-technical participation; (vi) Health and environmental education strategies; (vii) Responsibility for actions. Through this analysis it was possible to notice that even when the law, the terms of reference and the PMSB construction process itself present the importance of health issues within sanitation, focused on the promotional focus, the actions proposed within the municipal plans, do not pervade this theme, being mostly focused on environmental improvement with the implementation of engineering systems, except for some environmental education actions aimed at changing the habit of the population, which directly influence health. Therefore, an effort is needed so that these ambiguities are resolved so that sanitation guided by health promotion can contribute so that the principles and objectives set out in Law No. 11,445 / 2007 are achieved.